(untitled) (Medical Forum Monthly, 2024)
Objective: A cross sectional study to assess the level of awareness and knowledge of sanitary workers about infectious diseases, handling and disposal of hospital waste material. Study Design: A cross sectional study. Place and Duration of Study: A 600 bed tertiary care hospital of Rawalpindi district. Methodology: All sanitary workers working in the hospital for more than three months were interviewed by a doctor in the language which they understand. An anonymous, self descriptive, comprehensive questionaire was designed containing all information’s regarding experience, training of job and awareness regarding types and disposal of waste material etc. Results: Among 88 workers interviewed, (47.72%,n=42) were males and (52.28%,n=46) were females. Among them (39.78%,n=35) were having more than 5 years of experience as a sanitary worker. Only 4.54% had some training before joining their job. None of them were having medical checkup or vaccination before or during job. Majority were not using heavy duty gloves (76.14%,n=67), Apron (72.73%,n=64), industrial long shoes (93.19%,n=82), and masks (87.50%,n=77). Thirty one (35.32%) workers were dumping waste material in open and (64.78%,n=57) workers were dumping in isolated open place specified for the purpose. Forty eight (54.55%) workers were not using antiseptic or detergents for cleaning bedpans. Regarding hand washing practice, only (7.95%,n=07) workers were using some antiseptic. Majority were totally ignorant about infectious diseases (72.73%,n=64), handling of waste (81.81%,n=72), disposal of patient secretions (86.37%,n=67), used dressings, blood samples/bags (90.78%,n=79), injection vials/syringes (86.37%,n=76) and disposable items (82.96%,n=73). Conclusion: Handling of waste from the source to its final disposal should be done carefully under the supervision of trained staff. Training of the sanitry workers of the hospitals is required for this purpose. It will not only reduce the spread of infectious diseases, but also improve the health and efficency of the workers.